WEBSITE DEVELOPMENT DE LA ROSSA CAFÉ & RESTAURANT USING Macromedia Flash MX, PHP and MySQL - Ahmad Mursyidi (Jurnal Sistem Informasi, 2007)
Scientific writing is about making Website De La Rossa Cafe & Restaurant using Macromedia Flash MX, PHP and MySQL where the writing is addressed to the public to provide information about La Rossa Cafe & Restaurant Restaurant by promoting it by creating a website about the product owned by La Rossa Cafe & Restaurant, such as food, banqueting, and various wines on offer.